Mechanical Ventilation from Pathophysiology to Clinical Evidence - Bellani, Giacomo (Springer, 2022)
This publication is about pathophysiology and clinical protocols related to mechanical ventilation. Intended for professional public.
Keywords: pneumologie; Respiration, Artificial; Clinical Protocols; klinické protokoly; umělé dýchání; Pulmonary Medicine; anesteziologie a intenzivní lékařství